Enhancing Creativity and Critical Thinking in Secondary School Art Education through Innovative Methods - Aminova Sabina Anvar qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article examines effective strategies for enhancing creativity and critical thinking in secondary school art education. It explores interactive teaching methods, project-based learning, flipped classroom approaches, and technology integration as key tools to engage students actively in the learning process. The study provides practical recommendations for educators to foster student-centered learning and promote both technical and conceptual artistic competencies.